The productive potential of the land and its assessment principles in Ukraine - Butenko, E.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2017)
Getting the maximum economic effect on agricultural lands without environmental performance needs to restore these areas. The main objective of optimum utilization of land resources is a process of territorial organization, in which the need to apply the most effective option to use the whole complex of land resources for the greatest productive potential of agricultural land.The concept of "productive potential" is considered as the combination of characteristics of land and natural conditions, shaped by human society, and determine the nature of the rational use of land in the area of expanded reproduction. In general terms the maximum opportunity in the economy. The productive potential of land is not a sustainable figure. During the agricultural use of the land productive potential is constantly changing due to the gradual improvement or reduction of logistics, soil fertility and obtaining agricultural products.The productive capacity of agricultural land is proposed to assess the following indicators: a qualitative characterization of soils and agricultural technologies. These indicators are as diverse comparative calculation to be posted in stages.First of all, draws attention to the qualitative characteristics of the soil, which is the basis for growing crops. Data on basic indicators of soil to be correct and complex to define parameters of soil and expressed through generalized estimation of fertility. These figures are in agrochemical passport fields. The final calculation serves agrochemical and environmental agrochemical evaluation, filed in points.Modern agricultural technologies is a complex process operations management processes productive crops in artificial ecosystems to achieve the forecasted yields and product quality while ensuring environmental safety and some economic efficiency. Number of applied agricultural technologies depends on the complexity of environmental conditions and the level of planned productivity. The more intense agricultural technologies, especially natural factors must be considered.To improve performance and improvement of production in agriculture advanced countries in the world use precision agriculture. When used precision agriculture systems plant receives the amount of substances which it needs. By fertilizing spot, where they are needed, minimized costs of acquisitionEqually important set of measures aimed at improving the natural environment is reclamation. Thanks to the introduction of more productive land reclamation, increasing their resistance to adverse climatic conditions and creates an environment that best meets the requirements that are in agriculture.Bet the use of productive potential site is reduced to an objective assessment of the environmental and economic interests and study the most effective ways to implement them.Prevention of the costs of restoring soil quality and further increase the full net production effects that positively influence the formation of the productive potential of agricultural land. Key words: productive capacity, soil fertility, agricultural technologies, forecasting